SSI for Disabled Immigrants: Why Do Ethnic Networks Matter? - Furtado, Delia; Theodoropoulos, Nikolaos (American Economic Review, 2013)
Immigrants residing among many coethnics are especially likely to receive SSI for a disability when they belong to high SSI take-up immigrant groups. After showing that this relationship cannot be fully explained by differences in health, we consider the likely sources of these network effects by separately examining their role in the decision to apply for SSI and, conditional on applying, their role in determining who ultimately receives benefits. Our results suggest that networks may increase the probability of applying for SSI despite minor disabilities, but it is unlikely that network effects are driven by egregious lies on applications.